PLURALITAS MAZHAB DAN METODOLOGI ISTINBĀṬ HUKUM DALAM KONTEKS INDONESIA - Zaki Aqil Nashrullah; Anwar Hafidzi (Al Arsy: Journal of Education, Management and Islamic Thought, 2025)
This article examines the plurality of Islamic schools of law (madhāhib) and the methodology of legal reasoning (istinbāṭ al-ḥukm) from a normative–conceptual perspective within the Indonesian context. This article argues that madhhab plurality is a historical and epistemological reality that emerges from differences in juristic reasoning, socio-cultural conditions, and methodological approaches among classical Muslim scholars. Using a library-based and normative analytical approach, this study explores how various methods of istinbāṭ, such as qiyās, istihsān, and maṣlaḥah mursalah, contribute to the richness and adaptability of Islamic law in Indonesia. The findings indicate that plurality does not fragment Islamic law, but instead strengthens its normative framework by enabling legal interpretation to respond dynamically to social change. The paradigm of maqāṣid al-syarī‘ah functions as an integrative bridge between textual interpretation and contextual application, ensuring that Islamic law remains just, beneficial, and compatible with the national legal system. Therefore, madhhab plurality plays a strategic role in shaping a contextual, humanistic, and maslahat-oriented methodology of Islamic legal thought in Indonesia.